2016
DOI: 10.1002/term.2223
|View full text |Cite
|
Sign up to set email alerts
|

Adipose stromal cells differentiation toward smooth muscle cell phenotype diminishes their vasculogenic activity due to induction of activin A secretion

Abstract: Adipose stromal cells (ASCs) support endothelial cell (EC) vasculogenesis through paracrine and cell-contact communications. In addition, ASCs differentiate towards the smooth muscle cell (SMC) phenotype under different stimuli, which prompted their use as a source of mural cells in fabricating small calibre vessels. How ASCs' SMC-lineage commitment affects their subsequent communication with ECs is unknown. The vasculogenic characteristics of human ASCs in progenitor stage and after differentiation towards SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The secreted VEGF assessed by ELISA had a similar trend, which was highest at day 3, and decreased at days 5 and 7. Consistently, it was reported that mesenchymal stem cells (MSCs), such as ASCs, following their differentiation into smooth muscle cells downregulated VEGF expression while upregulating α-SMA, SM22α expression [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The secreted VEGF assessed by ELISA had a similar trend, which was highest at day 3, and decreased at days 5 and 7. Consistently, it was reported that mesenchymal stem cells (MSCs), such as ASCs, following their differentiation into smooth muscle cells downregulated VEGF expression while upregulating α-SMA, SM22α expression [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 80%
“…It was found that VEGF secretion is precisely orchestrated parallel to the different stages of the angiogenic process [ 11 , 12 ]. Other MSCs, such as bone marrow mesenchymal stem cells (BMMSCs) and adipose stem cells (ASCs), interact with ECs similarly, shifting their paracrine activity from being pro-angiogenic to angiostatic and phenotypes from stem cells to mural cells following the developmental progress of the vessel formation [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A carefully controlled balance of TGF‐β1‐dependent signaling pathways regulates cell differentiation , proliferation , migration , metastasis, and ECM production . Inappropriate alteration of this balance often occurs in the pathogenesis and progression of fibrosis‐related diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Activin A was indispensable in the early stages of ADSCs differentiation into vascular SMCs when cultured with ECs [50]. However, induction of activin A secretion after stimulating ADSCs towards SMCs diminished ADSCs’ vasculogenic activity [51]. The summary of mechanisms of ADSCs differentiation into SMCs is displayed in Figure 1.…”
Section: Subcutaneous Adipose-derived Stem Cellsmentioning
confidence: 99%